Regulations in assisted reproduction and patients' knowledge (Research, Society and Development, 2023)
Infertility is considered by the World Health Organization (WHO) as a global public health problem, affecting around 15% of the world population. In Brazil, there is no specific legislation regarding the treatment of infertility and the use of assisted reproduction techniques. The Federal Council of Medicine (FCM) is the one who, through ethical regulations, dictates the rules followed by the medical profession; and the latest published Resolution about it is the number 2.320/2022. The present study aims to investigate the level of knowledge of patients about these CFM regulations. A multicenter cross-sectional observational study was carried out at the Medicine Faculty of Itajubá (MG) and the LabFiv - Clínica Gera (SP). The research was carried out through a bibliographical survey and application of an online questionnaire (Google Forms) to couples who sought out help at the Gera Fertility and Human Reproduction Clinic (SP).  Our findings revealed a prevalence of 66% of patients who have knowledge regarding the Resolution of the Federal Medical Council; 64% are aware of the number of embryos placed in a straw; 56% are informed about the possibility of embryonic biopsy; 74% are aware of what to do with surplus embryos; 80% are conscious of the specific term provided by the laboratory after the decision to discard. Thus, it is concluded that the majority of patients have knowledge about the CFM regulations related to in vitro fertilization (IVF) and embryo cryopreservation.